Microfluidic production and characterization of biofunctionalized giant unilamellar vesicles for targeted intracellular cargo delivery. (January 2021) - Staufer, Oskar; Antona, Silvia; Zhang, Dennis; Csatári, Júlia; Schröter, Martin; Janiesch, Jan-Willi; Fabritz, Sebastian; Berger, Imre; Platzman, Ilia; Spatz, Joachim P.
Abstract: Lipid-based vesicles have found widespread applications in the life sciences, allowing for fundamental insights into membrane-based processes in cell biology and as carrier systems for drug delivery purposes. So far, mostly small unilamellar vesicles (SUVs) with diameters of ~100 nm have been applied as carrier systems for biomedical applications. Despite this progress, several systematic limitations have arisen due to SUV dimensions, e.g., the size and total amount of applicable cargo is limited. Giant unilamellar vesicles (GUVs) might offer a pragmatic alternative for efficient cargo delivery. However, due to the lack of reliable high-throughput production technologies for GUV-carrier systems, only little is known about their interaction with cells. Here we present a microfluidic-based mechanical droplet-splitting pipeline for the production of carrier-GUVs with diameters of ~2 μm. The technology developed allows for highly efficient cargo loading and unprecedented control over the biological and physicochemical properties of GUV membranes. By generating differently charged (between −31 and + 28 mV), bioligand-conjugated (e.g. with E-cadherin, NrCam and antibodies) and PEG-conjugated GUVs, we performed a detailed investigation of attractive and repulsive GUV-cell interactions. Fine-tuning of these interactions allowed for targeted cellular GUV delivery. Moreover, we evaluated strategies for intracellular GUV cargo release by lysosomal escape mediated by the pH sensitive lipid DOBAQ, enabling cytoplasmic transmission. The presented GUV delivery technology and the systematic characterization of associated GUV-cell interactions could provide a means for more efficient drug administration and will pave the way for hitherto impossible approaches towards a targeted delivery of advanced cargo such as microparticles, viruses or macromolecular DNA-robots.